2013
DOI: 10.1097/acm.0b013e3182864299
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Validity of the MCAT Exam in Relation to Academic Performance Through Medical School

Abstract: The combination of UGPAs and MCAT total scores performs well as a predictor of UP. Both UGPAs and MCAT total scores are strong predictors of academic performance in medical school through graduation, not just the first two years. Further, these relationships generalize across medical schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
65
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 12 publications
1
65
1
2
Order By: Relevance
“…The results showed evidence that students who had lower MCAT scores also exhibited academic struggles. However, it was not the case for the majority of the cohorts (4). Furthermore, the study also suggested colleges to continue to use both the college grade point average (GPA) and the MCAT together in their admissions screenings in order to yield stronger correlations to academic performance and student persistence.…”
Section: Literature Reviewmentioning
confidence: 90%
See 1 more Smart Citation
“…The results showed evidence that students who had lower MCAT scores also exhibited academic struggles. However, it was not the case for the majority of the cohorts (4). Furthermore, the study also suggested colleges to continue to use both the college grade point average (GPA) and the MCAT together in their admissions screenings in order to yield stronger correlations to academic performance and student persistence.…”
Section: Literature Reviewmentioning
confidence: 90%
“…From a student's perspective, they have resented the fact that one exam may be determining their career path. An AAMC national research study surveying 119 US medical school cohorts from 2001 to 2004 questioned the predictability of the MCAT exam (4). The results showed evidence that students who had lower MCAT scores also exhibited academic struggles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…5,6 The criterion could be a behavior 10 or a score on a test or measure. 5 Dunleavy et al 27 27 To establish the validity of the criterion, Dunleavy et al 27 argued that UP is an important criterion from the perspective of the student, medical school, and society. The reliability of the UP criterion was not discussed.…”
Section: Predictive Validitymentioning
confidence: 99%
“…The reliability of the UP criterion was not discussed. 27 The model with the best predictive validity using the UP criterion was the combination of UGPAs and MCAT total scores. 27…”
Section: Predictive Validitymentioning
confidence: 99%
“…Additionally, each school or program-specific mission will likely use different assessment methodologies or apply the information from assessments in different ways for their own locally driven purposes (Prideaux et al 2011;Cleland et al 2015). Low matriculant drop out combined with high pass rates (Kraft et al 2013;Dudek et al 2005;Tonesk and Buchanan 1987) are often taken as indication that current selection methods are adequate and successful (Dunleavy et al 2013). However, low drop out and high pass rates also means that selection committees are the primary gatekeepers to the profession.…”
mentioning
confidence: 99%